2006
DOI: 10.1093/humrep/del322
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis-generated mouse models of human infertility with abnormal sperm

Abstract: BACKGROUND: The aetiology of human male fertility, with impairment of sperm number, motility and morphology (oligoasthenoteratozoospermia), has been difficult to understand, partly for lack of animal models. METHODS: An ethylnitrosourea (ENU) mutagenesis strategy has been successful in producing heritable gene mutations with phenotypes similar to human male infertility, and here, we describe three independent ENU-induced mutations that cause a phenotype of oligoasthenoteratozoospermia in mice. RESULTS: The loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…This is in agreement with our earlier studies [7] that suggested that the axonemal doublet functions in part as anchor for the formation of the corresponding ODF: we demonstrated that Spag4 binds to the doublet followed by binding of Odf1 and other ODF proteins to Spag4. In a large mouse mutagenesis study [29] the Repro2 mutation was shown to result in elongated spermatids with an apparently normal axoneme, some aligned mitochondria and a disorganized array of ODF in the cytoplasm: these mice also suffer from dysplasia of the fibrous sheath [30]. Sperm tail abnormalities in humans have been classified in two groups [31-33]: a heterogeneous set of different sperm abnormalities as seen in low frequency in infertile men, and a specific set of sperm abnormalities seen in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with our earlier studies [7] that suggested that the axonemal doublet functions in part as anchor for the formation of the corresponding ODF: we demonstrated that Spag4 binds to the doublet followed by binding of Odf1 and other ODF proteins to Spag4. In a large mouse mutagenesis study [29] the Repro2 mutation was shown to result in elongated spermatids with an apparently normal axoneme, some aligned mitochondria and a disorganized array of ODF in the cytoplasm: these mice also suffer from dysplasia of the fibrous sheath [30]. Sperm tail abnormalities in humans have been classified in two groups [31-33]: a heterogeneous set of different sperm abnormalities as seen in low frequency in infertile men, and a specific set of sperm abnormalities seen in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An opposite strategy applies to the phenotype-based gene discovery process. The N-ethyl-N-nitrosourea (ENU)-induced chemical mutagenesis strategy is one of the available methods to generate point mutations in male mouse (and to lesser extend female) germ cells (Kennedy et al 2005, Handel et al 2006, Lessard et al 2007. Mice harboring the mutations are bred to homozygosity and reproductive tests are performed to identify mutations that cause infertility.…”
Section: Methods For Identifying Putative Epididymal Target Genesmentioning
confidence: 99%
“…[23][24][25][26][27][28] Knockout/knockin mice and gene-trapped mice The most common approach used to define a gene function in vivo is gene ablation by homologous recombination in embryonic stem (ES) cells, known as 'knockout' or 'gene targeting'. 29,30 This strategy is designed for the evaluation of a gene function on the basis of the complete elimination (null allele) or partially elimination of a candidate gene function (that is, deletion of particular domain(s) of the encoded protein).…”
Section: Different Types Of Mouse Modelsmentioning
confidence: 99%